Edukasi Fisioterpi Mengenai Kasus Neck Pain Akibat Terlalu Lama Bermain Handphone pada Pelajar SMK Ahmad Yani Jabung - Angga Pradipta; Wendy Yuhardhika Marta Prabawati; Dimas Sondang Irawan (Lembaga Pengembangan Kinerja Dosen, 2025)
Introduction : Neck pain is defined as pain experienced from the base of the head (occiput) to the upper part of the back and extends to the outer and upper borders of the shoulder blade (scapula). Excessive use of cellphones by continuously placing the head in the same position will cause weakness and fatigue in the neck muscles. Purpose : This education aims to explain the causes, symptoms and exercises that can be done independently to prevent ongoing pain. Method : The method used is by providing education to teenagers, with promotional media in the form of leaflets to make it more interesting and easy to understand which contains definitions, symptoms, risk factors and exercises to reduce the pain felt. Conclusion : The educational activities that have been carried out at Ahmad Yani Jabung Vocational School, Malang can provide students with knowledge and insight regarding neck pain so that they can increase their knowledge about how to prevent and treat neck pain independently by carrying out active exercises.